Integrated analytic hierarchy process and fuzzy analytic hierarchy process for Sahel watershed flood susceptibility assessment, Algeria - Elhadj Mokhtari; Brahim Abdelkebir; Abdelouahed Djenaoui; Nour El Houda Hamdani (Water Practice and Technology, 2024)
Effective disaster management heavily relies on accurate flood susceptibility mapping. The fuzzy analytic hierarchy process (FAHP) is adept at considering the imprecise nature of decision-making criteria. This study assesses FAHP's effectiveness in flood susceptibility mapping, comparing it with the conventional analytic hierarchy process (AHP). By using Geographic Information System-analyzed remotely sensed data, the research systematically evaluates flood risk southeast of Algiers. Various datasets, including Digital Elevation Model, slope, precipitation, and land use maps, were collected via remote sensing. A linear fuzzy membership function transformed the data into fuzzy values. AHP determined the importance of each dataset, with calculated weights multiplied by corresponding fuzzy values. Fuzzy analysis combined these characteristics into a five-category flood risk map, verified with Google Earth and satellite images. Results indicate a high potential for flood hazard mapping, categorizing 30% of frequently flooded regions as high risk. Maps reveal north basin areas are more flood prone due to excessive precipitation, and urban areas in floodplains are vulnerable. Receiver operating characteristic (ROC) curves and area under the ROC curve (AUC) assessments demonstrate AHP and FAHP's effectiveness. AUC values of 88.40 and 92% indicate that both models accurately predict flood-prone areas. FAHP excels, reducing subjectivity and ambiguity in human judgments. HIGHLIGHTS Fuzzy analytic hierarchy process (FAHP) excels in handling uncertain factors for accurate flood maps.; Utilizes diverse remote sensing data, converted into fuzzy values.; Comparative study in Sahel shows FAHP's superior performance (area under the receiver operating characteristic curve: 92%) in mitigating judgment uncertainty.; Maps reveal high susceptibility in heavily precipitated northern regions and floodplain urban areas.;